Determination of Young's modulus in aluminum alloys: Role of precipitates, dispersoids, and intermetallics - H.W. Doty; J. Hernandez-Sandoval; H.R. Ammar; V. Songmene; F.H. Samuel (Journal of Materials Research and Technology)
The present work was performed on Al–Si–Mg–Cu and Al–Si–Mg alloys containing measured amounts of Ni (0.4 wt% and 4 wt%), Bi (1.0 wt%), Ca (0.5 wt%), Sr (0.015 wt%), 10 vol%SiC(p), and 20 vol%SiC(p). After solutionizing treatment, tensile bars (ASTM B108) were aged in the temperature range of 155 °C–350 °C for up to 100 h. The results of 700 tensile bars show that although the value of E is the Σ = E1+E2+ E3 +----, where E is a function of interparticle spacing and particle volume fraction of each type of precipitate, E can not be determined using a simple empirical formula due to interference of other factors such as porosity, inclusions, particle/matrix surface reaction, and precision of measuring each of the involved parameters. Considering alloying elements, the addition of a sufficient amount of Ni (Ni/Cu > 1), in the T6 condition, produces the highest E value, about 92 GPa (Al2Cu, Al3Ni, Al3NiCu precipitates). Modification of the eutectic Si particles has a moderate improvement in E about precipitation hardening (about 12 %). The highest E value was obtained using metal matrix composites (359 alloy + 20 vol% SiC(p)) in the T6 condition, approximately 42 % improvement over that achieved using the base alloy, at 110 GPa.